POTENTIAL APPLICATION OF A LOCALLY SOURCED PHOTOCATALYST FOR THE PHOTOCATALYTIC DECOLOURISATION OF METHYL ORANGE IN AQUEOUS SOLUTION - F. A. AISIEN; N. A. AMENAGHAWON; O. I. URHOBOTIE (Journal of Engineering Science and Technology, 2015)
Periwinkle shell ash (PSA) was investigated for its photocatalytic properties in decolourising methyl orange in aqueous solution. The effects of irradiation time, initial dye concentration and PSA dosage on the decolourisation process were investigated. The optimum values of the process variables were: irradiation time, 50 minutes; initial dye concentration, 20 mg/L and PSA dosage, 3 g/L. The kinetics of the process was well described by the pseudo first order and Langmuir-Hinshelwood kinetic models while the adsorption equilibrium was well elucidated by both the Langmuir isotherm and Freundlich isotherm equations with high R2 values.